The effectiveness of physiotherapy for chronic headaches in patients with temporomandibular disorders: a systematic review - Quilghini, Charlène; Lefflot, Julian; Buchholtz, Kim (Frontiers in Rehabilitation Sciences, 2025)
BackgroundChronic headaches (CH) affect approximately 1 billion people globally, with women having three to five times higher prevalence. The estimated cost in Europe is €173 billion. Recent studies suggest a strong link between chronic headaches and temporomandibular disorders (TMD), which are characterized by orofacial pain, temporomandibular joint symptoms, and limited mandibular movement. Physiotherapy for these disorders often involves addressing muscle spasms through massage, trigger point therapy, and active stretching.ObjectiveThis systematic review aimed to assess the effectiveness of temporomandibular joint (TMJ) physiotherapy for patients with chronic headaches (CH) and temporomandibular disorders (TMD).MethodsA systematic literature search was performed in January 2025 using the PICOS framework and relevant MeSH terms across the PubMed, PEDro, and Cochrane databases. Two reviewers independently screened studies, with a third reviewer resolving disagreements. Five randomized controlled trials (RCTs) met the inclusion criteria. Data extraction and study characteristics were analyzed, and the risk of bias was assessed using the Cochrane RoB2 tool.ResultsThe review identified five studies, suggesting that physiotherapy may benefit these patients. Three studies showed significant improvements in headache intensity and frequency following TMJ or orofacial physiotherapy. One study favored the control group, and one showed no significant difference. However, variability in study quality, therapist roles, and poorly reported interventions limited comparability and prevented meta-analysis. The findings point to potential benefits of physiotherapy for managing chronic headaches and TMD but underscore the need for more standardized research.ConclusionThis review highlights the potential of multidisciplinary treatments for patients with chronic headaches and temporomandibular disorders. However, due to the variability in treatment protocols and outcome measures, further research is needed to confirm these findings and standardize protocols for more reliable and consistent results.